MAPPIT: a versatile tool to study cytokine receptor signalling. (19th November 2008) - Lemmens, Irma; Lievens, Sam; Tavernier, Jan
Abstract : MAPPIT (mammalian protein–protein interaction trap) is a cytokine receptor-based two-hybrid method that operates in intact mammalian cells. A bait is fused C-terminally to a STAT (signal transducer and activator of transcription) recruitment-deficient receptor, whereas the prey is linked to functional STAT-binding sites. When bait and prey interact a ligand-dependent complementation of the STAT recruitment deficiency occurs, leading to activation of a STAT-responsive reporter. MAPPIT is very well suited to study protein interactions involving activated cytokine receptors as the technique allows modification of the bait protein in a physiologically optimal environment.